2014
DOI: 10.1111/eth.12324
|View full text |Cite
|
Sign up to set email alerts
|

Neural Gene Expression Profiles and Androgen Levels Underlie Alternative Reproductive Tactics in the Ocellated Wrasse, Symphodus ocellatus

Abstract: Discrete variation in reproductive behavior and physiology is observed in diverse taxa. Although it is known that most within‐sex alternative reproductive tactics arise as a consequence of phenotypic plasticity, relatively little is known about differential neural gene expression among plastic alternative reproductive phenotypes. In the ocellated wrasse Symphodus ocellatus, males exhibit one of three alternative tactics (nesting, satellite, and sneaker) within a reproductive season, but switch tactics between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 67 publications
(247 reference statements)
4
50
1
1
Order By: Relevance
“…Previous work in this system has revealed somatic variation in gene expression among the male morphs that may be important in premating sexual selection (Stiver et al . ). Here, we focus on the consequences of postmating sexual selection on transcriptome evolution in the gonads.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous work in this system has revealed somatic variation in gene expression among the male morphs that may be important in premating sexual selection (Stiver et al . ). Here, we focus on the consequences of postmating sexual selection on transcriptome evolution in the gonads.…”
Section: Discussionmentioning
confidence: 97%
“…Satellites are in many ways intermediate, investing in premating behaviours as well as postmating competitive traits (Stiver & Alonzo ; Stiver et al . ). The three male types in this species therefore represent a continuum of pre‐ and postmating sexual selection.…”
Section: Introductionmentioning
confidence: 97%
“…However, within ARTs, differences in neural expression profiles can often be larger among male tactics than between males and females [18][19][20]. In bluegill, only two transcripts were consistently differentially expressed in females when compared to all male groups and these corresponded to gal and tac.…”
Section: Sex Differencesmentioning
confidence: 99%
“…These studies have found a large number of genes that vary among tactics in expression in the brain during mating. In the ocellated wrasse ( Symphodus ocellatus ), 1,048 genes were differentially expressed when comparing sneakers to two other male tactics (nesting and satellite) and to females [19]. In the black-faced blenny ( Tripterygion delaisi ) and peacock blenny ( Salaria pavo ), RNAseq identified approximately 600 transcripts differentially expressed within the brains of ‘sneaker’ versus other male tactics [18,20].…”
Section: Introductionmentioning
confidence: 99%